Colonization Ability and Impact on Human Gut Microbiota of Foodborne Microbes From Traditional or Probiotic-Added Fermented Foods: A Systematic Review - Roselli, Marianna; Natella, Fausta; Zinno, Paola; Guantario, Barbara; Canali, Raffaella; Schifano, Emily; De Angelis, Maria; Nikoloudaki, Olga; Gobbetti, Marco; Perozzi, Giuditta; Devirgiliis, Chiara (Frontiers in Nutrition, 2021)
A large subset of fermented foods act as vehicles of live environmental microbes, which often contribute food quality assets to the overall diet, such as health-associated microbial metabolites. Foodborne microorganisms also carry the potential to interact with the human gut microbiome via the food chain. However, scientific results describing the microbial flow connecting such different microbiomes as well as their impact on human health, are still fragmented. The aim of this systematic review is to provide a state of the art knowledge-base about the scientific literature addressing the connection between foodborne and gut microbiomes, as well as to identify possible gaps where more research is needed to clarify and map gut microorganisms originating from fermented foods, either traditional or added with probiotics, their possible impact on human gut microbiota composition and to which extent foodborne microbes might be able to colonize the gut environment. An additional aim was also to highlight experimental approaches and study designs which could be better standardized to improve comparative analysis of published datasets. Overall, the results presented in this systematic review suggest that a complex interplay between food and gut microbiota is indeed occurring, although the possible mechanisms for this interaction, as well as how it can impact human health, still remain a puzzling picture. Further research employing standardized and trans-disciplinary approaches aimed at understanding how fermented foods can be tailored to positively influence human gut microbiota and, in turn, host health, are therefore of pivotal importance.